Epidemiological study of the serology and geographic distribution of abortion causative agents in aceh cows in Indonesia - Muhammad Hanafiah; Amalia Sutriana; Teuku Zahrial Helmi; Ruhul Fajriah; Happy Mulyana; Cut Nanda Sabila; Nadhira Dewantara (Open Veterinary Journal)
Background: Abortion refers to the premature expulsion of a fetus from a dam, typically following the death of the fetus in utero. If fetal death occurs within the first 1–2 months of gestation, it is often classified as "early embryonic death." Such early losses generally proceed without noticeable clinical signs in the dam, and the termination of pregnancy may go undetected. In 2 months of gestation, fetal death usually results in evident clinical signs, culminating in the expulsion of the fetus and the associated fetal membranes.